2018
DOI: 10.1177/0959651818758910
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization and control of a magnetic shape memory alloy actuator using the modified generalized rate-dependent Prandtl–Ishlinskii hysteresis model

Abstract: In this article, two models are used, namely rate-independent and rate-dependent generalized Prandtl-Ishlinskii, to characterize a magnetic shape memory alloy actuator. The results show that the rate-independent model cannot consider the effect of input excitation frequency, while the rate-dependent model omits this drawback by defining a time-dependent operator. For the first time, the effects of excitation frequency on the hysteretic behavior of magnetic shape memory alloy actuator are investigated. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Because of the linear dependency of the normalized area of the hysteresis with respect to the excitation frequency, the proposed threshold function is formulated as [29]:…”
Section: Hysteresis Modelingmentioning
confidence: 99%
“…Because of the linear dependency of the normalized area of the hysteresis with respect to the excitation frequency, the proposed threshold function is formulated as [29]:…”
Section: Hysteresis Modelingmentioning
confidence: 99%
“…In other words, the voltage-induced heating rate affects the SMAs behavior. The study of frequency effect of current or voltage as a direct/indirect excitation on other smart materials such as piezoelectric, 48 pneumatic artificial muscle, 49 magnetic SMA, 18 and magnetostrictive 50 also shows that hysteresis loops become wider with increasing the frequency of current or voltage. The wider hysteresis indicates more dissipation of a system.…”
Section: Characterization Of Sma-driven Morphing Wingmentioning
confidence: 99%
“…Many researchers have tried to model the hysteresis behavior. 13–16 Hysteresis as a kind of internal loss of the material behavior emerges between the input and output of smart materials such as piezoelectric, 17 magnetic shape memory alloys (MSMAs), 18 magnetostrictive 19 , and magneto-rheological (MR) dampers. 20 SMAs hysteresis has a particular complexity because of its wide saturation curve and asymmetry in the heating and cooling paths.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the nonlinear and complex behavior of the SMA actuators is modeled precisely using this model. Shakiba et al 61 characterized a magnetic SMA actuator using rate-independent and rate-dependent generalized P–I. They used the proposed model to determine a proper range for controller coefficients during controller design.…”
Section: Introductionmentioning
confidence: 99%